“Prevalence of disordered eating and eating disorders among Norwegian university students before and after the COVID-19 pandemic, 2018 and 202.: The SHoT study.” - Lisa Marie Jacobsen; Gørill Haugan; Gina Dimitropoulos; Amelia Austin; Børge Sivertsen; Tonje Braaten; Ottar Bjerkeset (Journal of Eating Disorders)
Abstract Objective The prevalence of eating disorders (EDs) is increasing, but little is known about their trends among university students, particularly following COVID-19. This study examines prevalence in EDs and disordered eating (DE) symptoms among students in 2018 and 2022, focusing on gender and socio-demographic disparities. Methods Data were drawn from the Students’ Health and Well-being Study (SHoT) in 2018 (n = 50 054) and 2022 (n = 59 544), a large-scale Norwegian survey covering full-time university students aged 18–36. Participants completed self-report measures assessing symptoms of DE (EDS scale) and ED diagnoses, socio-demographic variables, lifestyle, gender identity and financial status. Statistical analyses included logistic regression to assess associations between factors known to be linked to DE and EDs, chi-square tests for group comparisons, and t-tests for continuous variables. Results From 2018 to 2022, the prevalence of self-reported EDs increased among females (3.5% in 2018 and 4.5% in 2022) and males (0.4% in 2018 and 0.6% in 2022), while gender-diverse students exhibited the overall highest ED rates (around 10% in both surveys). Anorexia nervosa remained the most common ED among females. Daily/almost daily exercise, financial difficulties, loneliness, and living alone were closely linked to EDs, odds ratios (ORs) ranging from 1.3 to 3.7 in females. Similar patterns were seen for female DE cases. Although numbers were low, financial difficulties and particularly loneliness indicated higher risk for DE and any EDs among males. Discussion The findings suggest a relative rise in ED prevalence among students after the COVID-19 pandemic, while DE symptoms and -cases only changed minimally. These findings highlight the need for enhanced awareness and student mental health services, particularly for gender-diverse individuals, and to improve early detection and intervention strategies among those facing financial hardship and loneliness.